2019
DOI: 10.1002/iub.2070
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐surface‐bound circulating DNA in the blood: Biology and clinical application

Abstract: Cell‐surface‐bound extracellular DNA (csbDNA) is present on the outer membrane of blood cells, including both red blood cells and leukocytes. Although less well characterized than cell‐free DNA (cfDNA) in plasma and serum, leukocyte and red blood cell csbDNA form a considerable fraction of the blood extracellular nucleic acids pool, with typically at least comparable amount of DNA occurring bound to the outer surface of cells as compared with circulating free DNA in plasma. The cellular origin of csbDNA is not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 78 publications
4
29
0
Order By: Relevance
“…Our study is focused on two specific autoantibodies, anti-DNA and anti-PS, because of their previously described roles in the pathogenesis of other diseases ( Pisetsky & Lipsky, 2020 ; Rivera-Correa & Rodriguez, 2020 ) and their capacity to bind to different cell types in the circulation ( Fernandez-Arias et al, 2016 ; Tamkovich & Laktionov, 2019 ). We observed that anti-DNA antibodies, which are typically found in autoimmune disorders, such as SLE ( Pisetsky, 2016 ) and in some infectious diseases ( Berlin et al, 2007 ), are found in 6% of COVID-19 patients in this cohort and correlate strongly with severity of COVID-19 disease in this group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study is focused on two specific autoantibodies, anti-DNA and anti-PS, because of their previously described roles in the pathogenesis of other diseases ( Pisetsky & Lipsky, 2020 ; Rivera-Correa & Rodriguez, 2020 ) and their capacity to bind to different cell types in the circulation ( Fernandez-Arias et al, 2016 ; Tamkovich & Laktionov, 2019 ). We observed that anti-DNA antibodies, which are typically found in autoimmune disorders, such as SLE ( Pisetsky, 2016 ) and in some infectious diseases ( Berlin et al, 2007 ), are found in 6% of COVID-19 patients in this cohort and correlate strongly with severity of COVID-19 disease in this group.…”
Section: Discussionmentioning
confidence: 99%
“…Because the levels of cell-free DNA and anti-DNA correlate with severity of disease and markers of cell injury, it is likely that the binding of anti-DNA to cell-free DNA contributes to the pathogenesis of COVID-19 manifestations. It is known that cell-free DNA binds to the surface of endothelial and immune cells (Tamkovich & Laktionov, 2019), as well as erythrocytes (Hotz et al, 2018), where it could constitute a target for anti-DNA antibodies in the circulation, triggering complement-mediated cell lysis. We observed a strong correlation of anti-DNA antibodies with lactate dehydrogenase (LDH) and creatine kinase, suggesting that anti-DNA antibodies may contribute to muscle injury, which is frequent in COVID-19 patients (Paliwal et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our study is focused on two specific autoantibodies, anti-DNA and anti-PS, because of their previously described roles in the pathogenesis of other diseases (14, 15) and their capacity to bind to different cell types in the circulation (18, 19). We observed that anti-DNA antibodies, which are typically found in autoimmune disorders, such as Systemic Lupus Erythematosus (20) and in some infectious diseases (21), are found in 13% of COVID-19 patients in this cohort and correlate strongly with severity of COVID-19 disease in this group.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that cell-free DNA binds to the surface of endothelial and immune cells (19), as well as erythrocytes (23), where it could constitute a target for anti-DNA antibodies in the circulation, triggering complement-mediated cell lysis. We observed a strong correlation of anti-DNA antibodies with lactate dehydrogenase (LDH) and creatine kinase, suggesting that anti-DNA antibodies may contribute to muscle injury, which is frequent in COVID-19 patients (24).…”
Section: Discussionmentioning
confidence: 99%
“…The enriched mitochondrial ctDNA is about 100 bp in size, much smaller than that of nuclear ctDNA, further displaying the size variety of ctDNA fragments ( 8 ). Notably, there are long-size cfDNA fragments that exist, such as 2 kb and 20 kb fragments, which are probably generated from cancer cell necrosis ( 25 ) and blood cell surface ( 26 ), respectively. The accurate enrichment of ctDNA in a particular interval size eliminates some background noises to some extent and relatively enhances data processing efficiency.…”
Section: Data Features Utilized By Current Ctdna Detection Strategiesmentioning
confidence: 99%